Larvicidal efficacy of six insecticides against culex quinquefasciatus say (Diptera: culicidae) larvae - Nasiruddin, Munira; Bhuiyan, Shaheda Yasmin (Journal of the Asiatic Society of Bangladesh, Science, 2016)
Searching for potent larvicidal toxic effects of six synthetic organophosphate insecticides (Diazinon 60 EC, Solar 55 EC, Malathion 57 EC, Delathroit 40 EC, Parathrin 10 EC and Clorasid 20 EC) were evaluated in the laboratory against 3rd or 4th instar larvae of the mosquito species, Culex quinquefasciatus Say. The tested insecticides: Diazinon (Dizinol) 60 EC, Solar (Chloropyrics 50% + Cypermethrin 5%) 55 EC, Malathion (Sithion) 57 EC, Delathroit (Dimehoate) 40 EC, Parathrin (Cypermethrin) 10 EC and Clorasid (Chloropyrics) 20 EC showed LC50 values at application dosages 0.00250-0.05 ppm, 0.0001-0.0025 ppm, 0.00025-0.005 ppm, 0.0005-0.001 ppm, 0.0001-0.002 ppm and 0.00025-0.0025 ppm to be 8.609×10-3 ppm, 4.440×10-4 ppm, 9.094×10-4 ppm, 24.215×10- 5 ppm, 4.797×10-4 ppm and 7.022×10-4 ppm respectively. Among the six insecticides, on the basis of LC50 and relative potency values, Delathroit 40 EC was the most toxic followed by Solar 40 EC > Parathrin 10 EC > Clorasid 20 EC > Malathion 57 EC > Diazinon 60 EC. J. Asiat. Soc. Bangladesh, Sci. 42(1): 13-20, June 2016